Experimental and computational fluid-structure interaction analysis and optimization of Deep-V planing-hull grillage panels subject to slamming loads – Part II: Irregular waves - Lee, Evan J.; Diez, Matteo; Harrison, Emily L.; Jiang, Minyee J.; Snyder, Lawrence A.; Powers, Ann Marie R.; Bay, Raymond J.; Serani, Andrea; Nadal, Maria L.; Kubina, Eric R.; Stern, Frederick (Ocean engineering, 2024)
The paper presents a comprehensive experimental and numerical study of the structural response of a planing hull in irregular waves. Two grillage panels are investigated: a traditionally designed grillage panel based on current structural design methods and an optimized grillage panel based on loads evaluated by computational fluid dynamics (CFD) in regular waves and mathematical optimization methods. The structural response of these two grillage panels in irregular waves is investigated both experimentally and numerically. Experiments and numerical simulations show that the largest impacts do not necessarily occur when the wave height is largest, but rather when there is a deep trough and the wave height is low. Comparing the structural response in irregular waves with the structural response in regular waves shows a reasonable correlation. Nevertheless, a more severe regular wave condition is needed to capture the wave impacts needed for structural design. Numerical simulations show that they can better predict the vertical acceleration of the center of gravity than current structural design methods. It is discussed how American Bureau of Shipping practices lead to safe but conservative structural designs and how current computational methods lead to more efficient design solutions. •FSI experiments and computations are shown for a high-speed GPPH model in irregular waves.•Uncertainty analysis is presented including deterministic and stochastic components.•Correlation between regular and irregular wave responses is discussed.•Validation of computations versus experiments (both original and optimized designs) is discussed.•Computational FSI lays the ground for more efficient designs than those produced by ABS rules.